Sustained PI3K Activation exacerbates BLM-induced Lung Fibrosis via activation of pro-inflammatory and pro-fibrotic pathways - Kral, Julia Barbara (Sci Rep, 2016)
Idiopathic pulmonary fibrosis (IPF) is a life-threatening disease with limited treatment options. Additionally, the lack of a complete understanding of underlying immunological mechanisms underscores the importance of discovering novel options for therapeutic intervention. Since the PI3K/PTEN pathway in myeloid cells influences their effector functions, we wanted to elucidate how sustained PI3K activity induced by cell-type specific genetic deficiency of its antagonist PTEN modulates IPF, in a murine model of bleomycin-induced pulmonary fibrosis (BIPF). We found that myeloid PTEN deficient mice (PTEN(MyKO)), after induction of BIPF, exhibit increased TGF-β1 activation, mRNA expression of pro-collagens and lysyl oxidase as well as augmented collagen deposition compared to wild-type littermates, leading to enhanced morbidity and decreased survival. Analysis of alveolar lavage and lung cell composition revealed that PTEN(MyKO) mice exhibit reduced numbers of macrophages and T-cells in response to bleomycin, indicating an impaired recruitment function. Interestingly, we found dysregulated macrophage polarization as well as elevated expression and release of the pro-fibrotic cytokines IL-6 and TNF-α in PTEN(MyKO) mice during BIPF. This might point to an uncontrolled wound healing response in which the inflammatory as well as tissue repair mechanisms proceed in parallel, thereby preventing resolution and at the same time promoting extensive fibrosis.